Status Kewarganegaraan Ganda Anak Hasil Perkawinan Campuran Warga Negara Indonesia dan Warga Negara Australia - Syifa Agustin (Al-Qadlaya : Jurnal Hukum Keluarga Islam, 2023)
When getting married, many people marry partners of different nationalities, for example a man with Indonesian citizenship marries a woman with Australian citizenship or vice versa. This is caused by the influence of globalization that is currently occurring. This marriage will certainly cause problems in determining citizenship status if the couple has children, especially if the couple is domiciled in Indonesia. Indonesia firmly does not apply dual citizenship status, in Law Number 12 of 2006 concerning Citizenship, except for children under certain conditions or what is called the principle of limited dual citizenship. This research is intended to find answers regarding the citizenship status of children born from mixed marriages between Indonesian citizens and Australian citizens as well as legal protection for children resulting from these mixed marriages. This research uses normative research methods through a conceptual approach. The author uses primary legal materials that are binding and also secondary legal materials as references. The results of this research are the dual citizenship status of children resulting from mixed marriages and their rights to receive preventive legal protection to ensure legal certainty as Indonesian citizens.